Institutional Foundations of Ukraine’s Transition to the Green Economy - Timoshenkov, Igor V.; Babenko, Vitalina; Nashchekina, O. M.; Makovoz, Oksana (Sciedu Press, Canada, 2020)
Possibilities and impediments to Ukraine transition to the Green Economy have been analyzed. The development and improvement of Ukraine environmental law have been determined as the obligatory condition of this transition. The main objectives of the environmental law improvement have been formulated: improving the quality and effectiveness of economic institutions, regulating social relationships in the sphere of environmental protection and assuring the environmental security of society. Codification of Ukraine environmental legislation and adoption of Ukraine environmental code have been characterized as the main way of achieving these objects.
Keywords: green economy; environmental law; environmental legislation; formal and informal institutions of environmental protection; effectiveness of institutions; quality of institutions; environmental code